A Bayesian mixed logit-probit model for multinomial choice - Martin Burda; Matthew Harding; Jerry Hausman (Centre for Microdata Methods and Practice (cemmap), 2008)
In this paper we introduce a new flexible mixed model for multinomial discrete choice where the key individual- and alternative-specific parameters of interest are allowed to follow an assumptionfree nonparametric density specification while other alternative-specific coefficients are assumed to be drawn from a multivariate normal distribution which eliminates the independence of irrelevant alternatives assumption at the individual level. A hierarchical specification of our model allows us to break down a complex data structure into a set of submodels with the desired features that are naturally assembled in the original system. We estimate the model using a Bayesian Markov Chain Monte Carlo technique with a multivariate Dirichlet Process (DP) prior on the coefficients with nonparametrically estimated density. We employ a 'latent class' sampling algorithm which is applicable to a general class of models including non-conjugate DP base priors. The model is applied to supermarket choices of a panel of Houston households whose shopping behavior was observed over a 24-month period in years 2004-2005. We estimate the nonparametric density of two key variables of interest: the price of a basket of goods based on scanner data, and driving distance to the supermarket based on their respective locations. Our semi-parametric approach allows us to identify a complex multi-modal preference distribution which distinguishes between inframarginal consumers and consumers who strongly value either lower prices or shopping convenience.
Keywords: C11; C13; C14; C15; C23; C25; 330; multinomial discrete choice model; Dirichlet Process prior; non-conjugate priors; hierarchical; latent class models; Probit-Modell; Bayes-Statistik; Markovscher Prozess; Diskrete Entscheidung; Konsumentenverhalten; SB-Lebensmittelgeschäft; USA